Prenatal muscle development in a mouse model for the secondary dystroglycanopathies. Issue 1 (December 2015) - Kim, Jihee; Hopkinson, Mark; Kavishwar, Manoli; Fernandez-Fuente, Marta; Brown, Susan
Abstract Background The defective glycosylation of α-dystroglycan is associated with a group of muscular dystrophies that are collectively referred to as the secondary dystroglycanopathies. Mutations in the gene encoding fukutin-related protein (FKRP) are one of the most common causes of secondary dystroglycanopathy in the UK and are associated with a wide spectrum of disease. Whilst central nervous system involvement has a prenatal onset, no studies have addressed prenatal muscle development in any of the mouse models for this group of diseases. In view of the pivotal role of α-dystroglycan in early basement membrane formation, we sought to determine if the muscle formation was altered in a mouse model of FKRP-related dystrophy. Results Mice with a knock-down in FKRP (FKRPKD ) showed a marked reduction in α-dystroglycan glycosylation and reduction in laminin binding by embryonic day 15.5 (E15.5), relative to wild type controls. In addition, the total number of Pax7+ progenitor cells in the FKRPKD tibialis anterior at E15.5 was significantly reduced, and myotube cluster/myofibre size showed a significant reduction in size. Moreover, myoblasts isolated from the limb muscle of these mice at E15.5 showed a marked reduction in their ability to form myotubes in vitro. Conclusions These data identify an early reduction of laminin α2, reduction of myogenicity and depletion of Pax7+ progenitor cells which would be expected to compromise subsequent postnatal muscle growth and its ability to regenerate postnatally. These findings are of significance to the development of future therapies in this group of devastating conditions.